Janus in governance: Interpellations around an educational policy of community intervention in Portugal - Antunes, Fátima; Barros, Rosanna (Education Policy Analysis Archives, 2019)
This article intends to empirically document the ambiguity, even ambivalence, of governance practices[1], through the study of a public policy in Portugal, the Programme InovAction, that stimulates intervention projects in ‘local state of emergency’ territories. In this way, we search to contribute to the debate around the reform of the State and public policies, apprehended through metamorphoses in the coordination of collective action in education. Education, State and governance are viewed as social relationships and sites of social practices; governance is understood as a field in which policies, discourses and practices manifest themselves in neo-liberal hegemonic versions or according to contradictory achievements. The data we mobilize were built on documental analysis and on information obtained through semi-structured interviews (to national, regional and local projects Coordinators, technicians and young people). The unfolding discussion illuminates tensions and contradictions in governance practices of Programme InovAction: the strengthening of collective action may occur simultaneously with the construction of routes and alternative spaces of social exclusion; the reduction of the social responsibility of the school with regards to certain audiences challenges approaches to the construction of a public space of education; the privilege given to known interests has gone side by side with practices to broaden the local governance circle.